A rigid-toughness balanced polypropylene composite material and preparation method thereof

By introducing POE-g-GMA and PLLA into polypropylene materials, a graft copolymer is generated and a "salami" structure is constructed, which solves the deficiencies in mechanical strength and toughness of polypropylene materials and achieves the material's rigid-tough balance and performance. promote.

CN118834471BActive Publication Date: 2025-01-24HANGZHOU NORMAL UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411320559.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-24
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

Existing polypropylene materials have shortcomings in terms of mechanical strength and toughness, especially under low temperature conditions and high requirements for impact performance, the performance of the materials is not sufficient to meet the needs of a variety of industrial applications.

Method used

By introducing reactive polyolefin elasty-methyl acrylic hydroglcel glycerin (POE-G-GMA) and polylactic acid (PLLA), the original POE-G-PLLA is generated in the process of processing. The new elastic body of high toughness and high modular volume is mixed with polypropylene to realize the original construction of the "SALAMI" structure to enhance the strength and toughness of the material.

Benefits of technology

The rigid balance of polypropylene materials has been achieved, and the impact strength and stretching performance of the material are significantly improved, so that it is suitable for a variety of industrial applications and meets the needs of high -performance materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118834471B_ABST
    Figure CN118834471B_ABST
Patent Text Reader

Abstract

The present invention discloses a rigid-toughness balanced polypropylene composite material and a preparation method thereof, and the method comprises: melt blending polyolefin-methacrylate glycidyl copolymer and polylactic acid through a mixer to obtain a uniform blend, then cooling to room temperature, adding it to polypropylene, and mixing uniformly at room temperature to obtain a mixture A; or directly mixing polyolefin-methacrylate glycidyl copolymer, polylactic acid, and polypropylene at room temperature to obtain a mixture B; selecting one of the mixtures A or B and adding it to a mixing device for melt blending, and finally obtaining a modified polypropylene composite material. The present invention realizes the high performance of polypropylene materials through specific formulas and processes, and is suitable for a variety of industrial applications; the preparation method is simple to operate and suitable for large-scale production. The composite material exhibits the characteristics of high-performance polymer alloys, and provides high-quality material selection for application fields requiring high strength and high toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer materials, and relates to a rigid-toughness balanced polypropylene composite material and a preparation method thereof. The composite material achieves a combination of high strength and high toughness through a specific formula and process, and is suitable for a variety of industrial applications. Background Art

[0002] Polypropylene (PP) is one of the five major general-purpose plastics. It is rich in sources, low in price, has excellent performance, good processing performance, and a wide range of uses. It is currently the most promising resin for the high-performance development of general-purpose plastics in the world. PP has a regular structure and has higher mechanical strength than polyethylene, good insulation performance, heat resistance and chemical resistance, etc., but it has poor low-temperature toughness, high notch sensitivity, poor dimensional stability of products, and is prone to bending deformation. It has poor weather resistance, light resistance, heat resistance and aging resistance, which limits its application in some fields. In order to improve the shortcomings of PP performance, rubber, thermoplastic elastomer and PP are usually blended to achieve toughening modification of PP to form a blend with excellent impact strength and low-temperature toughness.

[0003] Polyolefin elastomers (POE) are usually random copolymers with high α-olefin content obtained by copolymerizing ethylene and α-olefins (such as 1-butene, 1-octene) with metallocene catalysts. POE has good compatibility with polyolefin plastics (such as polyethylene, polypropylene, etc.) and can be used as a plastic modifier to significantly increase the flexibility and impact resistance of the material. The crystalline ethylene chains in the POE molecules can be used as physical crosslinking points to bear loads, and the amorphous ethylene and octene long chains can give it excellent high elasticity, high strength, high elongation and excellent low-temperature performance. However, POE has poor fluidity and its addition will greatly reduce the rigidity of the material. How to further improve the mechanical strength and modulus and prepare a blended material with excellent comprehensive performance and balanced rigidity and toughness is still the core scientific issue facing PP toughening modification. Summary of the invention

[0004] In view of the shortcomings of the above-mentioned prior art, the present invention proposes a method for preparing a new type of elastomer. Since the PLLA molecule contains a terminal carboxyl group, it has a high reactivity with the epoxy group. Therefore, a reactive polyolefin elastomer-glycidyl methacrylate (POE-g-GMA) is introduced into the blending system, so that the PLLA is directly melt-blended with the component containing the epoxy group, and the graft copolymer POE-g-PLLA is generated in situ during the processing process, so that the PLLA molecular chain is effectively fixed in the elastomer, and a new type of elastomer with both POE (high toughness) and PLLA (high modulus) components is prepared. Further, it is blended with PP as a toughening agent to realize the in-situ construction of the "salami" structure in the PP matrix. POE as the outer shell layer of "salami" can effectively reduce the interfacial tension between the matrix and the elastomer, improve the interphase adhesion, and promote the effective transmission of interfacial stress; PLLA as an inclusion in "salami" can give the material a certain rigidity and hardness, and finally obtain a PP blended material with a balance of rigidity and toughness and excellent comprehensive performance.

[0005] In order to achieve the above-mentioned object of the invention, on the one hand, the present invention provides a method for preparing a rigid-toughness balanced polypropylene composite material, which specifically includes the following steps:

[0006] S1. Melt-blending pellets or powders of polyolefin elastomer-glycidyl methacrylate copolymer and polylactic acid in a mass ratio of 3:7 to 7:3 to obtain a uniform blend; then, cooling the blend to room temperature, and adjusting the content of polyolefin elastomer-glycidyl methacrylate to 10 to 20 wt%; then, mixing it with polypropylene pellets or powder (accounting for 60 to 79 wt%) at room temperature to obtain a mixture A; or, directly adding pellets or powders of polyolefin elastomer-glycidyl methacrylate copolymer (accounting for 10 to 20 wt%) and polylactic acid (accounting for 9 to 20 wt%) to pellets or powder of polypropylene (accounting for 60 to 71 wt%), and mixing at room temperature to obtain a mixture B.

[0007] S2. Mixture A or B is put into a mixer and melt-blended at high temperature to ensure that all components are fully combined, and finally a polypropylene composite material with high strength and high toughness is obtained. This material is also called modified polypropylene.

[0008] As a preferred technical solution of the present invention, it also includes a step of pre-treatment and drying of the raw materials, and the specific operation is as follows:

[0009] The pellets or powders of polypropylene and polylactic acid are vacuum dried at a temperature of 60-80°C for 24-48 hours. The pellets or powders of polyolefin elastomer-glycidyl methacrylate copolymer are vacuum dried at a temperature of 40-50°C for 24-48 hours.

[0010] In addition, for the mixing equipment and process parameters for melt blending in step S1, the following conditions are preferred: the mixing equipment can be an internal mixer or an extruder. The rotation speed is set to 50-100 rpm, and the blending time is 10-15 min.

[0011] In step S2, the operating parameters of the mixing equipment are further clarified: when an internal mixer is used, the mixing speed is 50-100 rpm and the mixing time is 10-15 min. When an extruder is used, the mixing speed can be extended to 50-150 rpm.

[0012] Preferably, in steps S1 and S2, the temperature range for melt blending is 180-230°C.

[0013] According to another important aspect of the present invention, the present invention also provides a polypropylene composite material prepared by the method described in detail above. The composite material exhibits excellent properties due to its unique manufacturing process.

[0014] According to another important aspect of the present invention, the present invention also provides a use of the modified polypropylene prepared as above, which is directly applied as a masterbatch in the fields of automobiles, construction, chemicals, medical devices, agriculture, etc.

[0015] The high-strength, high-toughness polypropylene composite material and the preparation method thereof of the present invention can achieve the following significant advantages by implementing the above-mentioned optimized technical scheme:

[0016] 1) The polyolefin elastomer-glycidyl methacrylate copolymer used has re-reactivity, which enhances the processing performance of the material and the mechanical properties of the final product.

[0017] 2) The selected polylactic acid is an environmentally friendly biodegradable polymer material, which not only helps to improve the performance of composite materials, but also reduces the impact on the environment throughout the life cycle, which is in line with the concept of green manufacturing.

[0018] 3) The optimal ratio of each component of the rigid-toughness balanced polypropylene composite material described in the present invention is 60~79 wt% of base polypropylene, 15~20 wt% of polyolefin elastomer-glycidyl methacrylate copolymer, and 6~20 wt% of polylactic acid; the preparation process of the rigid-toughness balanced polypropylene described in the present invention involves a key reaction mechanism, namely, a new type of elastomer formed by polyolefin elastomer-glycidyl methacrylate copolymer and polylactic acid. Specifically, during melt blending, the epoxy group in POE-g-GMA undergoes a ring-opening reaction with the carboxyl group in PLLA to generate a graft copolymer POE-g-PLLA, thereby significantly improving the dispersion effect and toughening efficiency of the toughening agent. This elastomer effectively improves the strength and toughness of polypropylene materials by combining chemical reaction and physical blending.

[0019] 4) The present invention achieves the adjustability of the mechanical properties of modified polypropylene by finely controlling the ratio and addition amount of polyolefin elastomer-glycidyl methacrylate copolymer and polylactic acid during melt blending. This method opens up a new way to expand the application scope of polypropylene in different industries. In addition, the composite material prepared by the present invention exhibits the characteristics of high-performance polymer alloys, providing a high-quality material choice for application fields requiring high strength and high toughness.

[0020] 5) The advantage of the present invention is that it can be implemented with the help of conventional melt-mixing equipment, and its industrial preparation process is simple and efficient, and is very suitable for large-scale industrial production.

[0021] 6) In addition, the preparation method of the present invention also takes into account the proportion of each component and the processing conditions to ensure the optimal performance of the final product. This method is not only suitable for laboratory-scale research, but also suitable for industrial production and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The present invention will be described in more detail below through the accompanying drawings and specific embodiments. The accompanying drawings are intended to help understand the structure and working principle of the present invention, wherein:

[0023] Figure 1 Scanning electron microscope (SEM) images of Comparative Example 1 and Example 1 are shown. a and b in the figure correspond to the internal microstructure of each sample, respectively, and "1" and "2" represent SEM observation results with magnifications of 2 K and 10 K, respectively.

[0024] Figure 2 Transmission electron microscope (TEM) images of Comparative Example 1 and Example 1 are shown. Similarly, a and b represent the internal microstructure of each sample, and "1" and "2" correspond to TEM observation results at magnifications of 1.5 K and 6 K, respectively.

[0025] Figure 3 The comparative mechanical properties of Comparative Example 1 and Example 1 are shown.

[0026] The implementation mode, functional features and unique advantages of the present invention will be further described in conjunction with embodiments and with reference to the accompanying drawings. Please refer to these drawings and embodiments, which will provide a clearer explanation of the technical details of the present invention. DETAILED DESCRIPTION

[0027] The following content will be described in detail with reference to the accompanying drawings. It should be emphasized that these specific examples are only used to illustrate and illustrate the present invention and are not intended to limit the scope of the present invention. Without departing from the spirit of the present invention, any obvious modifications and variations should be included in the protection scope of the present invention.

[0028] In the following examples, unless otherwise specified, all technical terms have the meanings commonly understood by those skilled in the art. Similarly, unless otherwise specified, the experimental reagents used are all standard biochemical reagents, and the experimental methods also follow conventional operating specifications.

[0029] The raw materials used in the following examples and comparative examples are as follows: H501 type polypropylene (PP) substrate was purchased from Sumitomo Chemical Co., Ltd. (Tokyo, Japan), and the melt flow index of this PP at 230°C is 3.0 g / 10 min, 2.16 kg; the number average molecular weight of polylactic acid (PLLA) ranges from 5000 to 150000 g / mol; the manufacturer of polyolefin elastomer-glycidyl methacrylate copolymer (POE-g-GMA) is: Jiayirong (Shanghai) Co., Ltd., brand: SOG-03.

[0030] Comparative Example 1: Preparation of polypropylene composite material PP / POE-g-GMA, the raw material mass ratio is set to 85:15. The specific steps are as follows:

[0031] Step S1. Raw material drying: The PP pellets were vacuum dried at 80 °C for 24 h. Similarly, the POE-g-GMA pellets were vacuum dried at 50 °C for 24 h.

[0032] Step S2. Mixing raw materials: Add the dried POE-g-GMA pellets to the dried PP pellets, and mix them thoroughly at room temperature to ensure uniform dispersion.

[0033] Step S3. Melt blending: Add the uniformly mixed raw materials into an internal mixer. Melt blending is performed at a temperature of 190°C and a rotation speed of 50 rpm for 10 min. Through this process, a modified polypropylene composite material is finally obtained.

[0034] Comparative Example 2: Preparation of polypropylene composite material PP / POE-g-GMA, the raw material mass ratio is set to 90:10. The specific steps are as follows:

[0035] Step S1. Raw material drying: The PP pellets were vacuum dried at 80 °C for 24 h. Similarly, the POE-g-GMA pellets were vacuum dried at 50 °C for 24 h.

[0036] Step S2. Mixing raw materials: Add the dried POE-g-GMA pellets to the dried PP pellets, and mix them thoroughly at room temperature to ensure uniform dispersion.

[0037] Step S3. Melt blending: Add the uniformly mixed raw materials into an internal mixer. Melt blending is performed at a temperature of 190°C and a rotation speed of 50 rpm for 10 min. Through this process, a modified polypropylene composite material is finally obtained.

[0038] Comparative Example 3: Preparation of polypropylene composite material PP / POE-g-GMA, the raw material mass ratio is set to 80:20. The specific steps are as follows:

[0039] Step S1. Raw material drying: The PP pellets were vacuum dried at 80 °C for 24 h. Similarly, the POE-g-GMA pellets were vacuum dried at 50 °C for 24 h.

[0040] Step S2. Mixing raw materials: Add the dried POE-g-GMA pellets to the dried PP pellets, and mix them thoroughly at room temperature to ensure uniform dispersion.

[0041] Step S3. Melt blending: Add the uniformly mixed raw materials into an internal mixer. Melt blending is performed at a temperature of 190°C and a rotation speed of 50 rpm for 10 min. Through this process, a modified polypropylene composite material is finally obtained.

[0042] Based on the above comparative examples 1 to 3, the proportion of POE-g-GMA is kept the same, the balance is the proportion of PLLA + PP, and the raw materials are blended in two steps. The following embodiments 1 to 9 are respectively proposed, that is, the polyolefin elastomer-glycidyl methacrylate copolymer and polylactic acid are first melt-blended and then mixed with polypropylene to form a mixture.

[0043] Example 1: Preparation of polypropylene composite material PP / POE-30PLLA, fixed POE-g-GMA mass fraction of 15wt%, PLLA + PP accounted for 85wt%, wherein the POE-g-GMA / PLLA raw material mass ratio is 7:3. The specific steps are as follows:

[0044] Step S1. Raw material drying: PP and PLLA pellets were vacuum dried at 80 °C for 24 h. POE-g-GMA pellets were vacuum dried at 50 °C for 24 h.

[0045] Step S2. Pre-blending and mixing: The dried POE-g-GMA pellets and PLLA pellets were blended at 190 °C and 50 rpm for 10 min to obtain a uniform blend. After the blend was cooled to room temperature, it was added to the dried PP pellets. Under normal temperature conditions, the materials were fully mixed to ensure uniform dispersion to obtain the final mixture.

[0046] Step S3. Melt blending and modification: The mixture obtained in step S2 is added to an internal mixer. Melt blending is performed at a temperature of 190°C and a rotation speed of 50 rpm for 10 min. Through this process, a modified polypropylene composite material is finally obtained.

[0047] like Figure 1 As shown, Example 1 (POE-g-GMA toughened PP composite material) and Comparative Example 1 (POE-30PLLA toughened PP composite material) were subjected to SEM analysis (POE-g-GMA mass fraction was 15wt%). It can be seen that the addition of PLLA has a significant effect on the micromorphology of PP / POE-g-GMA blends. It is believed that this is due to the ring-opening reaction between the epoxy group of POE-g-GMA and the terminal hydroxyl group of PLLA during the melt blending process, forming a new chemical bond connection. This connection not only enhances the internal bonding force of the material, but also promotes the dispersion of the elastomer in the polypropylene matrix.

[0048] like Figure 2 As shown, TEM analysis of Example 1 and Comparative Example 1 shows that a unique "salami" structure is formed in the sample of Example 1, which is distributed in the PP matrix in the form of an island structure. Figure 1There is a good correspondence between the SEM images of Example 1. This is because PLLA is incompatible with the PP matrix, so that the PLLA grafted molecular chain is selectively dispersed in the POE-g-GMA phase, realizing the in-situ construction of the "salami" structure in the PP matrix. Among them, POE as the outer shell layer of "salami" can effectively reduce the interfacial tension between the matrix and the elastomer, improve the interphase adhesion, and promote the effective transmission of interfacial stress, so that when the material is subjected to impact stress, the matrix material can transfer the stress to the toughening agent dispersed phase well; at the same time, PLLA, as an inclusion of "salami", has high rigidity and hardness, so that the prepared polypropylene composite material maintains high toughness while also significantly improving its strength, thereby meeting the requirements of high-performance materials. By controlling the micromorphology of the blend, the synergistic improvement of the rigidity and toughness of the PP composite material is achieved, which explains the subsequent preparation of the rigid-toughness balanced PP blended material.

[0049] Performance Testing:

[0050] The modified polypropylene samples prepared in the above comparative example 1 and example 1 were subjected to notch impact and tensile tests respectively to characterize the mechanical properties of the samples.

[0051] For the impact test, a microinjection molding machine was used to prepare an impact specimen with a length of 80 mm, a width of 10 mm, and a thickness of 4 mm. The depth of the V-notch was 2 mm, and then placed at room temperature for 12 to 24 hours. According to the GB / T 16420-1997 standard, an impact test machine was used to perform an impact test on the specimen, and the pendulum energy used was 2 J.

[0052] For the tensile test, dumbbell-shaped tensile specimens with a length of 20 mm, a width of 4 mm, and a thickness of 2 mm were prepared by microinjection molding and left to stand at room temperature for 12 to 24 h. The specimens were tensile tested by a universal material testing machine at a tensile rate of 10 mm / min.

[0053] The mechanical properties of Example 1 and Comparative Example 1 were compared and tested. The results are as follows: Figure 3 shown.

[0054] Table 1 is a summary of the specific data of the mechanical properties of Example 1 and Comparative Example 1:

[0055] Table 1

[0056]

[0057] A comprehensive impact and tensile performance analysis was performed on Example 1 and Comparative Example 1. The results show that the impact strength of Comparative Example 1 is only about 9.7 kJ / m², and its Young's modulus and elongation at break are both at a low level. In contrast, Example 1 adopts a two-step blending strategy: POE-g-GMA is first blended with PLLA, and then the resulting blend is melt-blended with PP. This strategy significantly improves the performance of the material. Specifically, the impact strength of Example 1 reaches about 26.7kJ / m², which is nearly 175% higher than that of Comparative Example 1. This is mainly because the chemical bonds formed between POE-g-GMA and PLLA during the two-step blending process enhance the internal bonding force of the material, while the elastomeric properties of POE-g-GMA effectively improve the toughness of the material. In addition, the Young's modulus of Example 1 is about 0.92 GPa, which is significantly higher than 0.74 GPa of Comparative Example 1, which indicates that the modified PP-based composite material has also been significantly improved in terms of rigidity. The increase in elongation at break (from 898.2% in Comparative Example 1 to 950.0% in Example 1) further demonstrates the improvement in the tensile properties of the material, which enables it to exhibit better ductility and toughness when subjected to external forces.

[0058] In summary, through the two-step blending process in Example 1, a PP-based composite material with high impact strength and excellent tensile properties was successfully prepared.

[0059] Example 2: Preparation of polypropylene composite material PP / POE-50PLLA, fixed POE- g The mass fraction of -GMA is 15wt%, PLLA+PP accounts for 85wt%, and the mass ratio of POE-g-GMA / PLLA raw materials is 5:5. The specific steps are as follows:

[0060] Step S1. Raw material drying: PP and PLLA pellets were vacuum dried at 80 °C for 24 h. POE-g-GMA pellets were vacuum dried at 50 °C for 24 h.

[0061] Step S2. Pre-blending and mixing: The dried POE-g-GMA pellets and PLLA pellets were blended at 190 °C and 50 rpm for 10 min to obtain a uniform blend. After the blend was cooled to room temperature, it was added to the dried PP pellets. Under normal temperature conditions, the materials were fully mixed to ensure uniform dispersion to obtain the final mixture.

[0062] Step S3. Melt blending and modification: The mixture obtained in step S2 is added to an internal mixer. Melt blending is performed at a temperature of 190°C and a rotation speed of 50 rpm for 10 min. Through this process, a modified polypropylene composite material is finally obtained.

[0063] Example 3: Preparation of polypropylene composite material PP / POE-70PLLA, fixing the mass fraction of POE-g-GMA at 15wt%, PLLA+PP at 85wt%, wherein the mass ratio of POE-g-GMA / PLLA raw materials is 3:7. The specific steps are as follows:

[0064] Step S1. Raw material drying: PP and PLLA pellets were vacuum dried at 80 °C for 24 h. POE-g-GMA pellets were vacuum dried at 50 °C for 24 h.

[0065] Step S2. Pre-blending and mixing: The dried POE-g-GMA pellets and PLLA pellets were blended at 190 °C and 50 rpm for 10 min to obtain a uniform blend. After the blend was cooled to room temperature, it was added to the dried PP pellets. Under normal temperature conditions, the materials were fully mixed to ensure uniform dispersion to obtain the final mixture.

[0066] Step S3. Melt blending and modification: The mixture obtained in step S2 is added to an internal mixer. Melt blending is performed at a temperature of 190°C and a rotation speed of 50 rpm for 10 min. Through this process, a modified polypropylene composite material is finally obtained.

[0067] Example 4: Preparation of polypropylene composite material PP / POE-30PLLA, fixed POE-g-GMA mass fraction of 10wt%, PLLA + PP accounted for 90wt%, wherein the POE-g-GMA / PLLA raw material mass ratio is 7:3. The specific steps are as follows:

[0068] Step S1. Raw material drying: PP and PLLA pellets were vacuum dried at 80 °C for 24 h. POE-g-GMA pellets were vacuum dried at 50 °C for 24 h.

[0069] Step S2. Pre-blending and mixing: The dried POE-g-GMA pellets and PLLA pellets were blended at 190 °C and 50 rpm for 10 min to obtain a uniform blend. After the blend was cooled to room temperature, it was added to the dried PP pellets. Under normal temperature conditions, the materials were fully mixed to ensure uniform dispersion to obtain the final mixture.

[0070] Step S3. Melt blending and modification: The mixture obtained in step S2 is added to an internal mixer. Melt blending is performed at a temperature of 190°C and a rotation speed of 50 rpm for 10 min. Through this process, a modified polypropylene composite material is finally obtained.

[0071] Example 5: Preparation of polypropylene composite material PP / POE-50PLLA, fixed POE- g The mass fraction of -GMA is 10wt%, PLLA+PP accounts for 90wt%, and the mass ratio of POE-g-GMA / PLLA raw materials is 5:5. The specific steps are as follows:

[0072] Step S1. Raw material drying: PP and PLLA pellets were vacuum dried at 80 °C for 24 h. POE-g-GMA pellets were vacuum dried at 50 °C for 24 h.

[0073] Step S2. Pre-blending and mixing: The dried POE-g-GMA pellets and PLLA pellets were blended at 190 °C and 50 rpm for 10 min to obtain a uniform blend. After the blend was cooled to room temperature, it was added to the dried PP pellets. Under normal temperature conditions, the materials were fully mixed to ensure uniform dispersion to obtain the final mixture.

[0074] Step S3. Melt blending and modification: The mixture obtained in step S2 is added to an internal mixer. Melt blending is performed at a temperature of 190°C and a rotation speed of 50 rpm for 10 min. Through this process, a modified polypropylene composite material is finally obtained.

[0075] Example 6: Preparation of polypropylene composite material PP / POE-70PLLA, fixing the mass fraction of POE-g-GMA at 10wt%, PLLA+PP at 90wt%, wherein the mass ratio of POE-g-GMA / PLLA raw materials is 3:7. The specific steps are as follows:

[0076] Step S1. Raw material drying: PP and PLLA pellets were vacuum dried at 80 °C for 24 h. POE-g-GMA pellets were vacuum dried at 50 °C for 24 h.

[0077] Step S2. Pre-blending and mixing: The dried POE-g-GMA pellets and PLLA pellets were blended at 190 °C and 50 rpm for 10 min to obtain a uniform blend. After the blend was cooled to room temperature, it was added to the dried PP pellets. Under normal temperature conditions, the materials were fully mixed to ensure uniform dispersion to obtain the final mixture.

[0078] Step S3. Melt blending and modification: The mixture obtained in step S2 is added to an internal mixer. Melt blending is performed at a temperature of 190°C and a rotation speed of 50 rpm for 10 min. Through this process, a modified polypropylene composite material is finally obtained.

[0079] Example 7: Preparation of polypropylene composite material PP / POE-30PLLA, fixed POE-g-GMA mass fraction of 20wt%, PLLA + PP accounted for 80wt%, wherein the POE-g-GMA / PLLA raw material mass ratio is 7:3. The specific steps are as follows:

[0080] Step S1. Raw material drying: PP and PLLA pellets were vacuum dried at 80 °C for 24 h. POE-g-GMA pellets were vacuum dried at 50 °C for 24 h.

[0081] Step S2. Pre-blending and mixing: The dried POE-g-GMA pellets and PLLA pellets were blended at 190 °C and 50 rpm for 10 min to obtain a uniform blend. After the blend was cooled to room temperature, it was added to the dried PP pellets. Under normal temperature conditions, the materials were fully mixed to ensure uniform dispersion to obtain the final mixture.

[0082] Step S3. Melt blending and modification: The mixture obtained in step S2 is added to an internal mixer. Melt blending is performed at a temperature of 190°C and a rotation speed of 50 rpm for 10 min. Through this process, a modified polypropylene composite material is finally obtained.

[0083] Example 8: Preparation of polypropylene composite material PP / POE-50PLLA, fixing the mass fraction of POE-g-GMA at 20 wt%, PLLA+PP accounting for 80 wt%, wherein the mass ratio of POE-g-GMA / PLLA raw materials is 5:5. The specific steps are as follows:

[0084] Step S1. Raw material drying: PP and PLLA pellets were vacuum dried at 80 °C for 24 h. POE-g-GMA pellets were vacuum dried at 50 °C for 24 h.

[0085] Step S2. Pre-blending and mixing: The dried POE-g-GMA pellets and PLLA pellets were blended at 190 °C and 50 rpm for 10 min to obtain a uniform blend. After the blend was cooled to room temperature, it was added to the dried PP pellets. Under normal temperature conditions, the materials were fully mixed to ensure uniform dispersion to obtain the final mixture.

[0086] Step S3. Melt blending and modification: The mixture obtained in step S2 is added to an internal mixer. Melt blending is performed at a temperature of 190°C and a rotation speed of 50 rpm for 10 min. Through this process, a modified polypropylene composite material is finally obtained.

[0087] Example 9: Preparation of polypropylene composite material PP / POE-70PLLA, fixing the mass fraction of POE-g-GMA at 20wt%, PLLA+PP at 80wt%, wherein the mass ratio of POE-g-GMA / PLLA raw materials is 3:7. The specific steps are as follows:

[0088] Step S1. Raw material drying: PP and PLLA pellets were vacuum dried at 80 °C for 24 h. POE-g-GMA pellets were vacuum dried at 50 °C for 24 h.

[0089] Step S2. Pre-blending and mixing: The dried POE-g-GMA pellets and PLLA pellets were blended at 190 °C and 50 rpm for 10 min to obtain a uniform blend. After the blend was cooled to room temperature, it was added to the dried PP pellets. Under normal temperature conditions, the materials were fully mixed to ensure uniform dispersion to obtain the final mixture.

[0090] Step S3. Melt blending and modification: The mixture obtained in step S2 is added to an internal mixer. Melt blending is performed at a temperature of 190°C and a rotation speed of 50 rpm for 10 min. Through this process, a modified polypropylene composite material is finally obtained.

[0091] Table 2 is a summary of the specific data of the mechanical properties of the above Examples 1 to 9 and Comparative Examples 1 to 3 (the testing methods are the same as those of Example 1):

[0092] Table 2

[0093]

[0094] In order to further demonstrate the beneficial technical effects of the present invention, based on the above-mentioned Examples 1 to 9, Examples 10 to 18 corresponding to the above-mentioned Examples 1 to 9 are also proposed, and the only difference is that the two-step blending in Examples 1 to 9 is replaced by a one-step blending at room temperature, that is, polyolefin-glycidyl methacrylate copolymer and polylactic acid are added to polypropylene, mixed in one step to obtain a mixture, and then the mixture is melt-blended at a temperature of 190 ° C and a rotation speed of 50 rpm for 10 minutes to finally obtain a modified polypropylene composite material.

[0095] Table 3 is a summary of the specific data of the mechanical properties of the above Examples 10 to 18 and Comparative Examples 1 to 3 (the testing methods are the same as those of Example 1):

[0096] Table 3

[0097]

[0098] The present invention is further analyzed below in combination with Table 2, Table 3 and the above-mentioned Examples 1 to 18.

[0099] The impact properties of Examples 1, 10 and Comparative Example 1 were analyzed. The analysis results showed that the impact strength of Comparative Example 1 was about 9.7 kJ / m², while in the samples of Examples 1 and 10, the impact strength was significantly improved due to the grafting of PLLA into the elastomer. In particular, in Example 1, POE-g-GMA and PLLA were first blended by a two-step method, and then the obtained blend was melt-blended with PP. Compared with Example 10, this method further improved the impact strength of the modified polypropylene, thereby obtaining a PP-based composite material with higher toughness.

[0100] The impact properties of Examples 1-3 and 10-12, 4-6 and 13-15, 7-9 and 16-18 were analyzed. The analysis results show that with the increase of PLLA content (i.e., the decrease of PP content), the impact strength of the material is improved. However, when the PLLA content reaches a certain critical value, the notched impact strength of the material decreases significantly. We speculate that when the elastomer content remains unchanged, as the PLLA ratio increases, PLLA fails to achieve good dispersion in the elastomer microregion, which may be the reason for the decrease in impact strength.

[0101] The impact properties of Comparative Examples 1, 2, and 3 were compared and analyzed. It can be seen that the impact strength of the material is significantly improved with the increase of POE-g-GMA content.

[0102] The tensile properties of Examples 1 and 10 were analyzed with Comparative Example 1. The analysis results show that both Examples 1 and 10 exhibited higher Young's modulus and elongation at break. In particular, in Example 1, POE-g-GMA and PLLA were first blended by a two-step method, and then the blend was melt-blended with PP. This method further improved the Young's modulus and elongation at break of the modified polypropylene. This is because the two-step method promotes the fixation of PLLA in the elastomer (POE-g-GMA), thereby forming a "salami" structure, which can more effectively enhance the toughness of PP.

[0103] The tensile properties of Examples 1-3 and 10-12, 4-6 and 13-15, 7-9 and 16-18 were analyzed. The analysis results show that the Young's modulus of the material increases with the increase of PLLA content (i.e., the decrease of PP content). However, when the PLLA content reaches a certain critical value, the elongation at break of the material decreases significantly. This shows that when the PLLA content is high, although the rigidity of the material is enhanced, its plastic deformation ability is weakened.

[0104] The tensile properties of Comparative Examples 1, 2, and 3 were analyzed. The analysis results show that the Young's modulus of the material decreases with the increase of the POE-g-GMA content, which means that the rigidity of the material is reduced. At the same time, the elongation at break of the material increases, indicating that the plastic deformation ability of the material is enhanced. This trend shows that by adjusting the content of POE-g-GMA, the rigidity and toughness balance of the material can be regulated to a certain extent.

[0105] In summary, the comprehensive performance of the polypropylene composite material PP / POE-g-GMA / PLLA (POE-g-GMA mass fraction is 15% or 20wt%, PLLA+PP accounts for 85wt% or 80%, and the POE-g-GMA / PLLA raw material mass ratio is 7:3 or 5:5) is optimal. At this time, due to the ring-opening reaction between the epoxy group of POE-g-GMA and the carboxyl group in PLLA, its compatibility is significantly improved; at the same time, PLLA is incompatible with the PP matrix, so that PLLA is selectively dispersed in the POE-g-GMA phase, forming a unique "salami" structure, which is distributed in the PP matrix in an island structure. In the PP / POE-g-GMA / PLLA ternary system, two-step blending is better than one-step blending, and its superiority is mainly reflected in several aspects. First, this method can significantly improve compatibility, because the epoxy groups in POE-g-GMA can react chemically with the hydroxyl and carboxyl groups in PLLA to form a more stable interface bond, thereby improving the compatibility of the entire system. Secondly, the two-step blending allows PLLA and POE-g-GMA to fully react in the first step, increasing the reaction time, improving the efficiency of the grafting reaction, ensuring that more epoxy groups participate in the reaction, and enhancing the interfacial adhesion. In addition, this method can also improve dispersibility, ensure that PLLA is more evenly dispersed in the system, reduce phase separation in the blend, and improve the overall performance of the material. At the same time, the two-step blending can optimize the processing conditions and reduce the processing difficulties that may be encountered in the one-step method, such as selecting a processing temperature and time that is more suitable for the two materials, and then adjusting the processing parameters according to the good compatibility that has been formed, thereby improving the processing performance of the entire system. Finally, the two-step blending also helps to improve the stability of material performance, because a stable interface structure is formed in the first step, and when PP is added, the performance fluctuations of the entire system are small, and it is easier to control the performance of the final product. In general, the two-step blending method shows advantages over the one-step method in the PP / POE-g-GMA / PLLA ternary system by improving compatibility, reaction efficiency, dispersibility, optimizing processing performance, and enhancing performance stability. Through the two-step method, the comprehensive performance of each component of the incompatible blend was successfully improved, synergistic performance was achieved, and a high-strength and high-toughness polypropylene composite material was obtained. In addition, by precisely controlling the addition ratio of polypropylene, polyolefin elastomer-glycidyl methacrylate copolymer, and polylactic acid, the mechanical properties of the modified polypropylene composite material can be effectively adjusted, providing flexibility and customization to meet the needs of different application scenarios.

[0106] The above embodiments are only specific implementations of the present invention and are not intended to limit the scope of protection of the present invention. The scope of protection of the present invention covers all forms that conform to the technical solution of the present invention and its equivalent replacement. Any changes and adjustments that do not exceed the essence and necessary features of the technical solution of the present invention should be included in the scope of protection of the present invention. The specific scope of protection shall be subject to the attached claims.

Claims

1. A method for preparing a rigid-toughness balanced polypropylene composite material, characterized in that: The following steps are involved: S1. Melt-blending polyolefin elastomer-glycidyl methacrylate copolymer pellets or powders with polylactic acid pellets or powders in a mass ratio of 3:7 to 7:3 to obtain a uniform blend, then cooling to room temperature, fixing the content of polyolefin elastomer-glycidyl methacrylate to 15 to 20 wt %, and then adding the blend to 60 to 79 wt % of polypropylene pellets or powders, and mixing at room temperature to obtain a mixture A; the polylactic acid is L-type polylactic acid and contains terminal carboxyl groups; S2. Adding mixed material A into a mixing device for melt blending to obtain modified polypropylene.

2. The method for preparing the rigidity-toughness balanced polypropylene composite material according to claim 1, characterized in that: Before step S1, the raw material is dried as follows: The polypropylene and polylactic acid are vacuum dried at a temperature of 60-80°C for 24-48 h; the polyolefin elastomer-glycidyl methacrylate copolymer is vacuum dried at a temperature of 40-50°C for 24-48 h.

3. The method for preparing the rigidity-toughness balanced polypropylene composite material according to claim 1, characterized in that: In step S1, melt blending is performed using an internal mixer or an extruder at a rotation speed of 50-100 rpm and a blending time of 10-15 min.

4. The method for preparing the rigidity-toughness balanced polypropylene composite material according to claim 1, characterized in that: In step S2, the mixing equipment is a mixer or an extruder.

5. The method for preparing the rigidity-toughness balanced polypropylene composite material according to claim 4, characterized in that: The speed of the internal mixer is 50~100 rpm, and the blending time is 10~15min.

6. The method for preparing the rigidity-toughness balanced polypropylene composite material according to claim 4, characterized in that: The speed of the extruder blending is 50~100 rpm.

7. The method for preparing the rigidity-toughness balanced polypropylene composite material according to any one of claims 1 to 6, characterized in that: In steps S1 and S2, the temperature range for melt blending is 180-230°C.

8. A polypropylene composite material, characterized in that: The method is prepared by any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of PLA / PP alloy with high-toughness and high fluidity

    CN106543665A